1997
DOI: 10.1152/ajpregu.1997.273.5.r1612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of restraint stress on food intake and body weight is determined by time of day

Abstract: Three experiments were conducted to investigate the effect of restraint stress applied at different times of the light-dark cycle on feeding behavior and body weight of rats. Sprague-Dawley rats were restrained for 3 h in restraining tubes either at the start or the end of the light cycle. There was a significant reduction in food intake on the day of restraint and no change in food intake during a 10-day recovery period in either experiment. Reductions of food intake on the day of restraint were about the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
100
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 31 publications
14
100
1
3
Order By: Relevance
“…In females, feeding and drinking differed significantly between the breeds over time, where RJF showed an immediate behaviour change followed by a fairly rapid return to baseline, while the effects were more subtle in WL. In rodents, decreased feeding can be caused by both repeated [35] and acute stress [38], and time to retain normal feeding has been found to vary dependent on type and intensity of the stressor [33,38,48]. Foraging behaviour in the WL did not revert to baseline during the entire hour after stress, while in RJF it did so faster, and even increased over baseline after 10-15 minutes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In females, feeding and drinking differed significantly between the breeds over time, where RJF showed an immediate behaviour change followed by a fairly rapid return to baseline, while the effects were more subtle in WL. In rodents, decreased feeding can be caused by both repeated [35] and acute stress [38], and time to retain normal feeding has been found to vary dependent on type and intensity of the stressor [33,38,48]. Foraging behaviour in the WL did not revert to baseline during the entire hour after stress, while in RJF it did so faster, and even increased over baseline after 10-15 minutes.…”
Section: Discussionmentioning
confidence: 93%
“…This allowed us, for the first time, to assess effects of domestication on behavioural and endocrine stress responses in chickens. In particular, we focused on the recovery process and the return to normal levels of both behaviour and concentrations of the steroids, using a similar approach as in earlier research on stress recovery [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, would lead to differential consequences of chronic/ intermittent stressor exposure, in terms of both outcome and severity, for an individual. In support, the few studies that have examined this hypothesis have shown that restraint stress has different effects on body weight development and adrenal gland weight, depending on the time of day of stressor exposure (Rybkin et al (1997) and Perez-Cruz et al (2009), for review, see Koolhaas et al (2011)). …”
Section: Introductionmentioning
confidence: 95%
“…Stress is well known to produce changes in body weight in animal models as well [8][9][10][11][12][13][14][15][16]. In non-human primates, exposure to psychosocial stress results in reduced negative feedback regulation of cortisol secretion, suppression of the hypothalamic-pituitary-gonadal (HPG) axis and reproduction, and increased depressive behavior [17,18].…”
Section: Introductionmentioning
confidence: 99%